Single unit recording from olfactory cilia - Frings, Stephan; Lindemann, Bernd (Biophysical journal, 1990)
Sensory cilia from olfactory receptor cells can be pulled into a patch pipette located above the mucus layer of an olfactory mucosa. While the pipette does not form a tight electrical seal with the ciliary membrane, it nevertheless allows to record current transients driven by action potentials arising in the olfactory neuron. This method is an alternative to single-unit-recording with electrodes pushed into the mucosa and, in some respects, to patch clamp recordings from isolated olfactory cells. Its advantage is technical simplicity and minimal disturbance of the neuron from which signals are derived. Less than 5% of the chemosensitive apical surface of the neuron is covered by the pipette. The neuron remains in situ and its cilia remain covered with some mucus. (However, mucus is in part dissolved by the bathing solution). Odorant thresholds in the picomolar range were thus obtained.
Gesehen am 26.01.2017